Needs Analysis the Development of Ethnoscience-Based Batik (Ethnostik) on Material Changes Form in Elementary School - Amalia Dwi Oktaviani; Anatri Desstya (Elementary Teacher Education Program, Majalengka University, 2024)
This research is motivated by the need for ethnoscience-based teaching materials to increase student’s love for local wisdom in Indonesia. The purpose of this study: a) evaluate the shortcomings of the use of teaching materials, b) determine the teacher’s understanding of ethnoscience, c) describe the teacher’s experience in using ethnoscience-based teaching materials, d) analyze the urgency of Ethnosciense-Based Batik (ETHNOSTIK) teaching materials in elementary schools. The research design in Research and Development, 4D model on the define stage. The research subjects were 6 teachers from 4th grade of SDN 04 Lempong, SDN Telukan 02, SDN Gelaran 1, SD 06 Al Islam Al fajar Surakarta, SDIT Nurul Huda Pracimantoro. Data collection techniques used questionnaires and interviews. The data were analyzed descriptively. Triangulating sources and techniques tested data validity. The results of this study are: a) the lack of use of teaching materials in the aspect of materials and practically, b) teachers consider ethnoscience as the utilization of goods around, c) the application of the ethnoscience-based teaching materials by several teachers has positive impact on students, d) 100% of teachers agree to develop teaching materials on the phasing transition that raise the Laweyan Batik Solo process for elementary school students. Keywords: Teaching Materials; Ethnoscience; Batik